(untitled) (Estudios humanísticos. Geografía, historia y arte, 1995)
This article wants to offer a first contribution to the social history of the coal minig areas in León. The analysis focuses on three main subjects: women and children work, kinds of labour working day and discipline, and those aspects related to healthcare and accident rate. I deal especially with the legal regulations concerning these fields as well as the effects in the province of León in the period between 1850/60 and 1959.